Inhibition of corrosion of mild steel in simulated oil well waterby aqueous extract of Hibiscus rosa-sinensis flower - Balakrishnan Latha; Kaliyaperumal Kavitha; Rajendran Susai (Zaštita Materijala)
controlling the corrosion of mild steel in simulated oil well water (SOWW). Weight loss method reveals that 10 % v/v of the extract offers 82 % inhibition efficiency (IE) to mild steel (MS) immersed SOWW. The mechanistic aspects of corrosion inhibitive effect have been investigated by polarization study and AC impedance spectra. Polarization study reveals that the mixed type of inhibitor in the presence of inhibitor system. The corrosion inhibition effect is confirmed by the increase in the linear polarization resistance value and decrease in the corrosion current value. The protective layer is formed on the metal surface is confirmed by the AC impedance spectra. This is confirmed by the fact that there is increase in charge transfer resistance value and decrease in the double layer capacitance value. The adsorption of inhibitor molecule obey Langmuir adsorption isotherm. The protective coating is characterized by FTIR spectroscopy. It confirms that the inhibitor has coordinated with ferrous ion the metal surface through the active principle component of β-sitosterol, quercetin and kaempferol-3-xylosylglucoside. The surface morphology has been investigated by scanning electron microscopy (SEM). Hence, aqueous extract of Hibiscus rosa-sinensis flower with simulated oil well water good corrosive inhibitive effect on pipeline made of mild steel.